PENGARUH PRODUK, HARGA, TEMPAT, PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PIZZA HUT DELIVERY GRESIK - Adel Trudis Nurya Jeni (Jurnal Manajerial, 2019)
Abstract The purpose of this study was to determine whether the product, price, place and sales promotion variables partially had an influence on the purchasing decision at Pizza Hut Delivery Gresik. The type of data used is primary data. Primary data was obtained through direct interviews with the Pizza Hut Delivery Gresik Manager. The data analysis technique used is multiple linear regression whose purpose is to calculate the magnitude of the regression coefficient which will show the magnitude of the influence of the independent variables consisting of product variables, prices, places, and sales promotions on purchasing decisions. Based on the results of this study indicate that product variables, prices, places, and sales promotions partially influence the purchase decision variables.